أثر الالتزام بأخلاقيات التسويق في تحسين صورة المؤسسة دراسة حالة الشركة الوطنية للتأمين SAA بالشلف: The impact of commitment to marketing ethics on improving the image of service enterprise -Case study of the national insurance copany SAA of chlef - - ليندة حيمر; نورالدين شارف (Journal of North African Economies, 2025)
The study aimed to identify the impact of commitment to marketing ethics in improving the image of the service institution from the point of view of customers, with the application to the customers of the National Insurance Company Agency (SAA) in Chlef, where the questionnaire tool was used to collect primary data from a soft sample consisting of (235) customers of the company's customers, the questionnaire included 39 phrases according to the five-point Likert scale distributed on three axes, the first axis was devoted to the general characteristics of the research sample, while the second was devoted to measuring the company's commitment to marketing ethics. According to the Code of Marketing Ethics of the American Marketing Association, the third axis was dedicated to measuring the image of the company After conducting appropriate statistical analyzes of the collected data, the study found a statistically significant impact between the company's commitment to marketing ethics in its six dimensions (honesty, transparency, justice, respect, responsibility, citizenship) and its mental image, and it was also found that commitment to justice came in first place, followed by commitment to honesty, then respect and transparency, responsibility and finally citizenship, and the The study recommended the need to develop and adopt a code of marketing ethics at the company level, and to train and motivate employees to adhere to it and work with it to establish a positive image among its customers.